Recent progress in two-dimensional graphdiyne: Synthesis, characterization, and applications - Dinh Phuc Do; Eunji Lee; Viet Q. Bui; Hyoyoung Lee (ChemPhysMater)
Graphdiyne (GDY) is a novel carbon allotrope that has attracted significant attention owing to its unique structural and electronic properties. Comprising sp2- and sp-hybridized carbon atoms, GDY forms a two-dimensional structure via conjugated −C≡C−C≡C− linkages. These linkages result in a highly π-conjugated system with a natural bandgap that distinguishes GDY from other carbon materials such as graphene. This review systematically provides an overview of GDY, with a focus on its intrinsic properties and synthesis strategies, techniques to characterize its structure, and recent advanced applications. First, we summarize several GDY synthesis strategies, providing a detailed discussion of the advantages and disadvantages associated with each approach. Subsequently, several practical and precise techniques, including solid nuclear magnetic resonance, Raman, Fourier-transform infrared, and X-ray photoelectron spectroscopies, transmission electron microscopy, and selected area electron diffraction, to characterize the GDY structure are discussed. Next, we elucidate the unique structural and electronic properties of GDY using both theoretical frameworks and experimental methodologies. Finally, we comprehensively discuss the recent applications of GDY in various fields, including biomedicine, electronics, optoelectronics, energy storage, and catalysis.